(untitled) (Proceedings of International Conference on Special Education, 2015)
Learning methods that process the sensory motor in all children. The process of Sensory motor in our view as Inclusion curriculum approach to a more modern approach to nature and we give naturally a normal proceed for both normal children and children who has difficulty, so that they later ready and capable of reading, writing, and counting. In the implementation of this process, the student brought in a play that it becomes his world; children’s world is a world of play for inclusion or jointly between normal children and special need children.Limitation to know very basic maturity on the child should achieve at the age of 4, where all men are generally normal been able to enable the entire movement of rough and smooth motor And we Neuro Senso Institution also have prepared a basic value’s tools . It could be we value on the completeness of Sensory motor all children , with Coordination competence. Who make it by playing while learning or learning by doing; the children that we prepare the very basic skills in advance have includes: 1) speed to respond something; (Body Awareness) 2) Have good concentration; 3) exercising self control; (Body Image) and 4) self-awareness about the time and place (body orientation) – they understand about how long, and where they are located. Sensory motor process optimize the development of a sensory system to function with full potential which is divided into three aspects, namely: 1) psychomotor; 2) audio motor; and 3) visual motor for age play 2.5 up to the age of 6 years old. Indeed the need of once sensory motor ambitions began to age an infant up to 6 year old children, that we can valued their ability of the children, to be able to enter into the world of reality and at the age of 4 years old child assessment, so that we can find the strength and weakness of the child, where the child is not too late if it should still be helped. And or starting to get developed talents and Gifted of children individually, because each child is unique: With: Psycho motor A Learning system that aims to build a physical advances, the thoughts, and emotions as a whole (holistic).In other words, is to improve the psycho-socio-emotional of the child. Audio motor A Learning system that aims to specifically to enhance the concentration and motor planning also an orientation spaces, and improve children’s overall communication skills. Visual motor A Learning system that aims specifically to help blend of fine motor coordination, rugged motor with eyes and ears, as well as to improve the development of cognition and perception of the child as a whole.